Expanding the capillary electrophoresis-based glucose unit database of the GUcal app. (12th December 2019) - Jarvas, Gabor; Szigeti, Marton; Campbell, Matthew P; Guttman, Andras
Abstract: GUcal is a standalone application for automatically calculating the glucose unit (GU) values for separated N -glycan components of interest in an electropherogram and suggests their tentative structures by utilizing an internal database. We have expanded the original database of GUcal by integrating all publicly available capillary electrophoresis (CE) data in the GlycoStore collection (https://www.glycostore.org ) and with in-house measured GU values. The GUcal app is freely available online (https://www.gucal.hu ) and readily facilitates CE-based high throughput GU value determination for first line structural elucidation.